Corporate instinct : building a knowing enterprise for the 21st century - Koulopoulos, Thomas (Van Nostrand Reinhold New YorkUS, 1997)
Outlines the basic principles of corporate instinct and the ways of applying and managing corporate instinct. Provides examples from dozens of companies where corporate instinct has been created and used successfully. Includes a corporate IQ test.